Method of stylisation as a way to improve the quality of professional art education and formation of author's stylistics - Konstantin Alexandrovich Parkhomenko (Obutchénie)
The Lugansk State Academy of Culture and Arts, named after Mikhail Matusovsky, served as the foundation for this study. Within the Faculty of Fine and Decorative Arts, specifically at the Department of Graphic Design, tailored tasks were integrated into individual courses. This approach enabled the assessment of students' initial artistic and imaginative thinking skills and facilitated their development. This method facilitated the evaluation of students' foundational artistic and imaginative thinking abilities, while also fostering their continued growth. The article examines stylization as a vital instrument that bolsters memory, imagination, and the cultivation of creative skills. Its goal is to create a methodological framework designed to enhance the quality of education. The stratometric method was utilized as the main technique for identifying creative groups, leading to the selection of eight groups for the experiment. This paper examines the practical method of stylization in special drawing classes for design students and its impact on the development of spatial thinking through assignments related to the stylization of architectural buildings and marine life objects. All groups were trained in graphic design and each group had between 10 and 17 participants. The artistic method shows that the study of the structural formation of an object lays the foundation for the creation of artistic works. Careful analysis and comparative evaluation of the creative works revealed results that emphasise the importance of this method for the development of professional skills and the formation of a unique personal style. The study suggests that there may be value in considering a greater focus on form analysis and comparison methods within the educational framework. It also points to the potential benefit of exploring ways to incorporate innovative techniques and creative assignments into the curriculum, with a view to maintaining and celebrating national traditions and characteristics.